Treatment of foot and ankle nonunions using supplemental allograft-derived proteins: A case series - Brian Burgess, DPM, FACFAS; Amber Kavanagh, DPM, AACFAS; Paul DeFrino, MD; David Garras, MD (Foot & Ankle Surgery: Techniques, Reports & Cases)
Arthrodesis of joints in the foot and ankle is a common treatment for end-stage arthritis, however the risk of nonunion remains apparent. The use of various orthobiologic agents to aid in bony union has shown to be beneficial due to ease of use, wide availability, and lack of autograft-associated donor site morbidity. The purpose of this study was to evaluate the use of bone graft combined with supplemental allograft-derived proteins in subjects who underwent surgical treatment for nonunion. A retrospective chart review of three surgeons was completed and found 16 patients undergoing revision fusion procedures for confirmed nonunion at 29 total articulation sites in the foot and ankle with an average follow up time of 12.7 months. Fusion across each joint was assessed using serial radiographs independently reviewed by a single, independent radiologist. Successful fusion was demonstrated in 28 out of 29 articulations (96.6 %) by six months, with an average time of 2.9 months to full fusion. No adverse events related to the graft, procedure, or hardware were reported. Supplemental allograft-derived proteins may be a safe and effective additive to support bony remodeling in arthrodesis procedures in the foot and ankle.